Challenges to the Ecological Environment: Deflection in Kincaid’s and Whitehead’s Narratives - Gautam, Mani Bhadra (Tribhuvan University Journal, 2025)
This paper critiques the human stupidity and challenges seen in the ecological environment as the people are doing unnatural activities in destroying the natural resources. The issues raised in this paper are taken from Jamaica Kincaid’s Among Flowers: A Walk in the Himalayas and Neil L. Whitehead’s “South America/Amazonia: The Forest of Marvels,”and they are studied from eco-ethical perspectives. This study is made with an objective of finding out the reasons for ecological degradation. This paper follows a qualitative research method and the texts are analyzed on the basis of primary and secondary resources for which texts and relevant references are studied comparatively. Methodological implication of the theories helps to explore environmental risk factors inscribed in Kincaid’s and Whitehead’s narratives in a comparative framework. This paper questions to the loopholes left in the early research and addresses them. Environmental and ecological theorists’ ideas support for completion of the paper. Finding of this paper is that the natural disasters which we are facing in the present time bring a critical condition soon. Previous studies do not support biospheric protection well and so this study helps to create an eco-friendly atmosphere.